PHILOSOPHICAL MEANINGS OF TRADITIONAL CUISINE RENDANG MINANGKABAU AS A CULTURAL HERITAGE OF INDONESIA - Nita Novianda Tanjung; M. Manugeren; Purwarno Purwarno (AICLL: ANNUAL INTERNATIONAL CONFERENCE ON LANGUAGE AND LITERATURE, 2020)
This research is related to the philosophical meanings of traditional cuisine Rendang Minangkabau as a cultural heritage of Indonesia. The research is conducted by means qualitative descriptive. The theory used is taken from the philosophy. Philosophy is the mother of all the sciences that have material objects and formal objects, objects the material is the mind while the object formal philosophy of science is truth, goodness and beauty in a manner dialogue. (Syafiie, 2010). This study explained the meanings of the philosophy in Rendang Minangkabau cuisine. Rendang is revered in Minangkabau culture as an embodiment of the philosophy of musyawarah, discussion and consultation with elders. The results show there are four meanings in each of the ingredients Rendang Minangkabau: Meat (dagiang) symbolizes Niniak Mamak (paman) and Bundo Kanduang (ibu) refers to the traditional clan leaders (respect for the parents). The coconut milk (karambia) symbolizes the Cadiak Pandai refers to the intellectuals (learning). The chilli (lado) symbolizes Alim Ulama refers to the religious leaders (uplifting Islamic laws). The spice mixture (pemasak) symbolizes the rest of Minangkabau society refers to the each individual (unity). This philosophy was indeed made to maintain the integrity of the Minang community in West Sumatra and also as a cultural heritage of Indonesia.